Underestimated Benefits from Periphery: Internal Migration and Subjective Well-being - Angela Kopmann; Katrin Rehdanz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper is among the first to link internal migration and subjective well-being in developed countries. Economic theory predicts that individuals migrate towards urban agglomerations, if the potential gain in income is sufficient to cover costs. However, this narrow view cannot explain why migration exists also to the rural periphery. In our analysis, we investigate non-monetary benefits beyond economics from internal migration. Using highly disaggregated spatial information on people s migration decisions and their subjective well-being from 2006 to 2010 for Germany, we control for selection bias by applying an individual fixed effect model with additional controls on the labor market region level. We find positive benefits from migration, which are positive and diminishing with distance. Urban-to-rural migration provides higher benefits than rural-to-urban migration in general. Older generations derive large negative benefits from rural-to-urban migration, but positive benefits from urban-to-rural migration. The latter suggests that economic theory underestimates benefits from migration to the periphery when ignoring non-monetary compensating differentials.
Keywords: A12; C33; R23; 330